Effect of Carbon Fibre Reinforced Polymer Laminates on Steel Fibre Reinforced Concrete Beams - Krishna kumar, Madhavaperumal, Mahamood-ul-hasan, Karthic (International Journal of Advanced Science and Technology, 2020)
The objective of this study is to investigate the flexural strength and crack propagation characteristic of reinforced concrete beam with CFRP (Carbon Fibre Reinforced Polymer) laminates. CFRP laminates is bonded with epoxy resin at the soffit (tension face) of the beam. Straight hooked end steel fibres are randomly reinforced in the beam as additive up to 1% of volume of concrete. Four-point bending flexure test to complete failure were conducted on 6 beams (2 beams strengthened with single layer CFRP laminate 2 beams with two layer CFRP laminates and 2 conventional RC beam). The yield load, ultimate load carrying capacity, ductility ratio, deflection and crack propagation of the beam were measured and compared with conventional beam to investigate the strengthening effects of single layer CFRP laminate and two layer CFRP laminates.